Co‐Anchoring of Engineered Immunogen and Immunostimulatory Cytokines to Alum Promotes Enhanced‐Humoral Immunity. Issue 7 (7th April 2022) - Chang, Jason Y. H.; Agarwal, Yash; Rodrigues, Kristen A.; Momin, Noor; Ni, Kaiyuan; Read, Benjamin J.; Moyer, Tyson J.; Mehta, Naveen K.; Silva, Murillo; Suh, Heikyung; Melo, Mariane B.; Wittrup, K. Dane; et al.
Abstract: Protein antigens are often combined with aluminum hydroxide (alum), the most commonly used adjuvant in licensed vaccines; yet the immunogenicity of alum‐adjuvanted vaccines leaves much room for improvement. Here, the authors demonstrate a strategy for codelivering an immunostimulatory cytokine, the interleukin IL‐21, with an engineered outer domain (eOD) human immunodeficiency virus gp120 Env immunogen eOD, bound together to alum to bolster the humoral immune response. In this approach, the immunogen and cytokine are co‐anchored to alum particles via a short phosphoserine (pSer) peptide linker, promoting stable binding to alum and sustained bioavailability following injection. pSer‐modified eOD and IL‐21 promote enhanced lymphatic drainage and lead to accumulation of the vaccine in B cell follicles in the draining lymph nodes. This in turn promotes enhanced T follicular helper cell priming and robust germinal center responses as well as increased antigen‐specific serum IgG titers. This is a general strategy for codelivery of immunostimulatory cytokine with immunogens providing a facile approach to modulate T cell priming and GC reactions toward enhanced protective immunity using the most common clinical vaccine adjuvant. Abstract : Alum is the most common clinical vaccine adjuvant; however, alum often elicits weak immune responses when combined with subunit protein antigens. Here, the authors develop a strategy to boost the immune response by co‐anchoring vaccine antigens and the cytokine interleukin‐21 (IL‐21) to alum particles; IL‐21 acts as a molecular adjuvant to enhance the antibody response against the antigen.